2012
DOI: 10.1111/j.1552-6569.2011.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

The Optic Radiation and the Cerebellar Peduncles in Adolescents with First‐Admission Schizophrenia —A Diffusion Tensor Imaging Study

Abstract: Our findings of altered fiber integrity in the optic radiations in adolescents with schizophrenia are in line with gray matter alterations in the visual cortices previously reported in the same sample and are in accordance with other studies that found decreased fractional anisotropy in these regions. These findings support the view that the visual system plays an important role in the pathogenesis of schizophrenia and may enhance our understanding of associations between the visual cortex and symptoms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…39 However, the middle cerebellar peduncle (MCP) which carries input fibers from the contralateral cerebral cortex to the cerebellar cortex via the pons was not significantly lowered in adolescents with first-admission or chronic schizophrenia patients. 40,41 We also documented that the MCP was not disordered in our patients (for further details see Table S2 in the online supplement).…”
Section: Discussionsupporting
confidence: 67%
“…39 However, the middle cerebellar peduncle (MCP) which carries input fibers from the contralateral cerebral cortex to the cerebellar cortex via the pons was not significantly lowered in adolescents with first-admission or chronic schizophrenia patients. 40,41 We also documented that the MCP was not disordered in our patients (for further details see Table S2 in the online supplement).…”
Section: Discussionsupporting
confidence: 67%
“…Contrary to our findings, several studies on the connectivity of thalamo-cortical networks in patients with SZ have reported that patients with SZ show no significant differences in functional or structural connectivity of the occipital cortex with the thalamus compared with HCs [ 64 66 ]. Conversely, patients with SZ display significantly decreased FA in optic radiations compared with HCs [ 67 , 68 ]. Optic radiation structure and correlations of structure measures with visual masking performance in patients with SZ were investigated [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The affected WM regions seem to be more widespread with a less consistent pattern of differences. Most EOS studies have generally identified less extensive frontal, 67,68,85,92 temporal, 49,86 parietal 69,70 and occipital 49,68,139 WM differences in patients compared to NC but there have also been three studies from the same research group using track-based spatial statistics (TBSS) reporting widespread findings. 55,90,91 WM tracts in EOS also seem to follow different maturational trajectories as inferred by FA compared to adult samples.…”
Section: Ii) Fes/ros Subjectsmentioning
confidence: 99%